2008
DOI: 10.1002/adfm.200701027
|View full text |Cite
|
Sign up to set email alerts
|

Novel Three Dimensional Cubic Fm3m Mesoporous Aluminosilicates with Tailored Cage Type Pore Structure and High Aluminum Content

Abstract: Novel three dimensional cubic Fm3m mesoporous aluminosilicates (AlKIT‐5) with very high structural order and unprecedented loadings of Al in the silica framework have been successfully prepared for the first time by using non ionic surfactant as a template in a highly acidic medium. The obtained materials have been unambiguously characterized in detail by several sophisticated techniques such as XRD, N2 adsorption, HRTEM, HRSEM, EDS, elemental mapping, 27Al MAS NMR, and NH3‐TPD. We also demonstrate that the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 40 publications
5
59
0
Order By: Relevance
“…www.chemeurj.org showed higher catalytic activity for acetylation of veratrole and ring opening of epoxides than the zeolites and other metal-substituted mesoporous materials. [17,52] However, the catalytic activity of AlKIT-5 in the synthesis of coumarin derivatives is less than that of KIT-5A C H T U N G T R E N N U N G (100)-20TA. This is mainly due to the presence of a huge number of acidic sites on the surface of the KIT-5 support that come from the TFA molecules and are easily available to the reactant molecules.…”
Section: Catalystsmentioning
confidence: 97%
See 1 more Smart Citation
“…www.chemeurj.org showed higher catalytic activity for acetylation of veratrole and ring opening of epoxides than the zeolites and other metal-substituted mesoporous materials. [17,52] However, the catalytic activity of AlKIT-5 in the synthesis of coumarin derivatives is less than that of KIT-5A C H T U N G T R E N N U N G (100)-20TA. This is mainly due to the presence of a huge number of acidic sites on the surface of the KIT-5 support that come from the TFA molecules and are easily available to the reactant molecules.…”
Section: Catalystsmentioning
confidence: 97%
“…Very recently, Vinu et al reported the preparation of aluminum-supported mesoporous KIT-5 material (AlKIT-5), which possesses a 3D mesostructure with Fm3m symmetry and excellent textural characteristics. [17] Although the material showed excellent performance in the acid-catalyzed reactions, the acidity of the material is much lower than zeolites and zeotype materials. By increasing the acidity of the KIT-5 materials, the possibility of using the material as a catalyst for various acid-catalyzed organic transformations could be extended.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous materials can be attractive materials for many kinds of applications [278][279][280], because these materials provide huge surface areas and pore volumes as well as well-defined pore geometries [281][282][283][284][285][286][287][288]. Research on mesoporous materials is currently extremely popular and detailed descriptions can be found in several reviews [289][290][291][292][293][294][295] and reports on advanced functions [296][297][298][299].…”
Section: Hybridization With Nanomaterials Toward Hierarchic Assembliesmentioning
confidence: 98%
“…[4][5][6][7][8][9][10] With respect to that, mesoporous materials that possess three-dimensional cage-type pore structures such as SBA-1, SBA-16, and KIT-5 are nowadays considered more promising as they are more resistant to pore blocking, they allow for a faster diffusion of the reactants, and they provide more adsorption sites, which are more accessible through the three-dimensional porous structure. [11] Mesoporous molecular sieves have received considerable attention owing to their narrow pore-size distributions, high surface areas, and large pore volumes. [12][13][14][15][16] Among the materials mentioned above, KIT-5 is particularly interesting as it possesses a highly ordered three-dimensional mesoporous structure with cubic Fm3m close-packed symmetry, a large surface area, pores with tunable diameter, a large specific pore volume, and large cages.…”
Section: Introductionmentioning
confidence: 99%